2016
DOI: 10.1038/srep38985
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profiling of Preneoplastic and Neoplastic Lesions of Oral Cavity Tissue Samples Revealed a Biomarker Pattern

Abstract: Oral cancer is a major health challenge in the Indian subcontinent and a dreadful form of cancers worldwide. The current study is focused on the identification of distinguished metabolites of oral cancer tissue samples in comparison with precancerous and control tissue samples using gas chromatography coupled with triple quadrupole tandem mass spectrometry and chemometric analyses. Metabolites obtained were identified through National Institute of Standards and Technology (NIST) mass spectral (Wiley registry) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The study on metabolomics of cancer tissue specimens is helpful to improve the diagnosis and treatment of OSCC. Currently, metabolomics studies of oral cancer use primarily biological fluids (e.g., plasma, urine, saliva) and cell lines (18)(19)(20)(21)(22), because biofluids and cell lines are readily available. Most biofluids-based metabolomics studies are relatively quantitative, without in-depth study on a specific metabolic type and a specific metabolite, such as amino acid metabolism and the specific content of a certain amino acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study on metabolomics of cancer tissue specimens is helpful to improve the diagnosis and treatment of OSCC. Currently, metabolomics studies of oral cancer use primarily biological fluids (e.g., plasma, urine, saliva) and cell lines (18)(19)(20)(21)(22), because biofluids and cell lines are readily available. Most biofluids-based metabolomics studies are relatively quantitative, without in-depth study on a specific metabolic type and a specific metabolite, such as amino acid metabolism and the specific content of a certain amino acid.…”
Section: Discussionmentioning
confidence: 99%
“…It is very important to study the metabolic mechanism of oral cancer progression, which will help improve the diagnosis and treatment of oral cancer. Many studies have confirmed that OSCC tissues undergo significant metabolic changes compared to normal tissues, such as lactate, glycine, proline, and hydroxyproline, 3AMP, uracil, spermidine, and c-glycosyltryptophan, 2-hydroxyglutarate, and glycerol-3monophosphate high expression in tumor tissues (21,27). The metabolic pathways associated with oral cancer mainly include glycolysis, amino acid metabolism and pentose phosphate pathway, and RNA biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the samples for the metabolomics study of OSCC were biofluids (eg. plasma, urine, saliva) and cell lines (16)(17)(18)(19), tissue samples were rarely reported (20), the most important reason is that biofluids are readily available. Most studies are based on biofluids metabolomics to distinguish from cancer patients to healthy control people, we need to use tissue samples to further study the metabolomics of OSCC, which can not only distinguish the cancer tissue from the normal paired tissue, but also study the metabolic pathway leading to carcinogenesis, so as to find therapeutic targets for cancer in the field of metabolomics.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary metabolomic analysis of OSCC tissue not only revealed differences between the metabolomic characteristics of cancer and normal tissues but also suggested that specific metabolic systems play a role in OSCC tissues [13]. Downregulated amino acid levels might be associated with enhanced energy metabolism, and the upregulation of the biosynthetic pathway might reflect the desired cellular proliferation in cancer cells [14]. Metabolites can be transferred through tissue compartments to the blood stream, promoting tumor growth and aggressive tumor behavior [15].…”
Section: Introductionmentioning
confidence: 99%